1985
DOI: 10.1002/clc.4960080808
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial infarction in the diabetic patient

Abstract: Summary: It has long been thought that the symptomatology and prognosis of coronary events in patients with diabetes may differ from those in nondiabetic persons. A review of recent data demonstrates a higher mortality during the acute phase of myocardial infarction for diabetic patients than for their nondiabetic counterparts, possibIy related to a higher incidence of congestive heart failure and cardiogenic shock. The clinical course of diabetic patients with infarction and the role of insulin in myocardial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
20
0
1

Year Published

1988
1988
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 43 publications
2
20
0
1
Order By: Relevance
“…Interestingly, complaints of chest pain were more common in Type 2 diabetic patients than in normal controls, which is surprising considering the previous data suggesting chest pain may be less common for a given degree of ischaemia. In the meta-analysis by Kereiakes et al [23] , the risk of myocardial infarction was the same in men and women with diabetes but women had a 40% greater mortality. This is supported by data from Framingham, where Abbott et al [26] demonstrated that diabetes doubled the risk of recurrent myocardial infarction in women, compared with both normoglycaemic women and diabetic men.…”
Section: Gender Differences; Diabetes and Myocardial Infarctionmentioning
confidence: 95%
See 2 more Smart Citations
“…Interestingly, complaints of chest pain were more common in Type 2 diabetic patients than in normal controls, which is surprising considering the previous data suggesting chest pain may be less common for a given degree of ischaemia. In the meta-analysis by Kereiakes et al [23] , the risk of myocardial infarction was the same in men and women with diabetes but women had a 40% greater mortality. This is supported by data from Framingham, where Abbott et al [26] demonstrated that diabetes doubled the risk of recurrent myocardial infarction in women, compared with both normoglycaemic women and diabetic men.…”
Section: Gender Differences; Diabetes and Myocardial Infarctionmentioning
confidence: 95%
“…Patients with diabetes who suffer a myocardial infarction have a poorer prognosis both acutely [21,22] and in the long term [23][24][25][26][27][28] . The Gotebö rg Trial [25] showed that the 5-year mortality post-myocardial infarction was 46% in diabetic population compared with 27% in normoglycaemic controls.…”
Section: Myocardial Infarctionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 The increased mortality in patients with diabetes in the setting of acute myocardial infarction has been demonstrated in numerous studies, and the mortality after acute myocardial infarction in patients with diabetes is approximately twice that of nondiabetic patients. [2][3][4] A significant increase in the number of necrotic cardiomyocytes in ventricular myocardial biopsies obtained from diabetic patients was reported recently. 5 Rosiglitazone (ROSI, Avandia) is a peroxisome proliferatoractivated receptor-␥ (PPAR-␥) agonist and the most potent member of the thiazolidinedione antidiabetic agents and was recently approved by the FDA for treatment of type II diabetes mellitus.…”
mentioning
confidence: 86%
“…Obesity, dyslipidemia, hypertension, and insulin resistance/glucose intolerance as well as a proinflammatory and prothrombotic state, characteristics of metabolic syndrome (Grundy et al, 2004), are thought to contribute to the accelerated atherosclerosis (Kannel and McGee, 1979;Uusitupa et al, 1993) and postmyocardial infarction mortality seen in type 2 diabetics (Kereiakes 1985;Woodfield et al, 1996). One of the potential mechanisms that may contribute to vascular disease in these patients is endothelial dysfunction, evidenced by impaired endothelium-dependent vasodilation and augmented responses to vasoconstrictors in preclinical models of metabolic syndrome (Walker et al, 1997(Walker et al, , 1999.…”
mentioning
confidence: 99%